2019
DOI: 10.1016/j.ccell.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

p53 Is a Master Regulator of Proteostasis in SMARCB1-Deficient Malignant Rhabdoid Tumors

Abstract: Highlights d Smarcb1-deficient mosaic GEM models recapitulate malignant rhabdoid tumors (MRTs) d Autophagy and UPR are essential adaptive mechanisms to proteotoxic stress in MRTs d The MYC-p53 axis regulates proteostasis in SMARCB1deficient cells d Autophagy and proteasome inhibitors achieve durable responses in MRT models

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 63 publications
12
70
0
Order By: Relevance
“…These results further support the link between Myc and protein synthesis in ATRT cells. Moreover, the correlation of Myc activity and SMARCB1-deficient cancers has been identified in priors studies [26][27][28]. Alimova et al found that SMARCB1-deficient ATRTs expressed higher Myc activity compare to normal brain tissues, regardless of the subtypes of ATRTs [28].…”
Section: Discussionmentioning
confidence: 98%
“…These results further support the link between Myc and protein synthesis in ATRT cells. Moreover, the correlation of Myc activity and SMARCB1-deficient cancers has been identified in priors studies [26][27][28]. Alimova et al found that SMARCB1-deficient ATRTs expressed higher Myc activity compare to normal brain tissues, regardless of the subtypes of ATRTs [28].…”
Section: Discussionmentioning
confidence: 98%
“…In this study we have interrogated the interactions between SMARCB1 loss, cellular differentiation state, and transcriptional changes associated with tumorigenesis, while generating a cellular model which will have utility for future mechanistic studies as well as for identification of potential therapeutic vulnerabilities in SMARCB1-deficient cells. While other systems of SMARCB1 loss or reintroduction have been used to study the mechanisms underlying ATRT in a controlled manner (Wilson et al 2010;Han et al 2016;Nakayama et al 2017;Wang et al 2017;Carugo et al 2019;Langer et al 2019), this complementary system has the benefit of using human cells, having the flexibility to take into account the effects of differentiation processes, and using SMARCB1 loss alone without additional oncogenic drivers, consistent with the human tumor phenotype (Lee et al 2012). In addition, similar to a recent publication (Langer et al 2019), our study provides an interrogation of the interactions between SMARCB1 loss and neural development, however, here we illustrate novel insight into the dramatic phenotypic differences which can occur with loss of SMARCB1 at different stages of differentiation, such as lethality in pluripotent cells and impairment of neuronal commitment and maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, RMC is resistant to the standard VEGF-directed therapies used for ccRCC and other RCC subtypes. A study of mosaic mouse models with inactivated SMARCB1 demonstrated that SMARCB1-negative tumors such as RMC are vulnerable to proteasome and autophagy blockade [34]. The sensitivity of RMC to proteasome inhibitors was further validated in a study of RMC cell lines [35].…”
Section: Kidney Cancer Geneticsmentioning
confidence: 99%